Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Lie bracket of vector fields is defined in two ways:

Let $\Phi^X_t$ be the flow associated with the vector field $X$, and let $d$ denote the tangent map derivative operator. Then the Lie bracket of $X$ and $Y$ at the point $x \in M$ can be defined as $[X, Y]_x := \lim_{t \to 0}\frac{(\mathrm{d}\Phi^X_{-t}) Y_{\Phi^X_t(x)} - Y_x}t = \left.\frac{\mathrm{d}}{\mathrm{d} t}\right|_{t=0} (\mathrm{d}\Phi^X_{-t}) Y_{\Phi^X_t(x)}$

or equivalently $[X, Y]_x := \left.\frac12\frac{\mathrm{d}^2}{\mathrm{dt}^2}\right|_{t=0} (\Phi^Y_{-t} \circ \Phi^X_{-t} \circ \Phi^Y_{t} \circ \Phi^X_{t})(x) = \left.\frac{\mathrm{d}}{\mathrm{d} t}\right|_{t=0} (\Phi^Y_{-\sqrt{t}} \circ \Phi^X_{-\sqrt{t}} \circ \Phi^Y_{\sqrt{t}} \circ \Phi^X_{\sqrt{t}})(x)$

How does one show by math that these two definitions are equivalent? And for the second definition, how does one show that $\left.\frac12\frac{\mathrm{d}^2}{\mathrm{dt}^2}\right|_{t=0} (\Phi^Y_{-t} \circ \Phi^X_{-t} \circ \Phi^Y_{t} \circ \Phi^X_{t})(x) = \left.\frac{\mathrm{d}}{\mathrm{d} t}\right|_{t=0} (\Phi^Y_{-\sqrt{t}} \circ \Phi^X_{-\sqrt{t}} \circ \Phi^Y_{\sqrt{t}} \circ \Phi^X_{\sqrt{t}})(x)$?

share|cite|improve this question

Let $c(t)= \psi_{-t} \circ \phi_{-t} \circ \psi_t \circ \phi_t(p)$. In his book A comprehensive introduction to differential geometry, Spivak shows that $c'(0)=0$ and $c''(0)=2[X,Y]_p$ (Prop. 15 and Thm. 16, p. 160-163).

To simplify the notations, he defines $$\begin{array}{l} \alpha_1(t,h)= \psi_t \circ \phi_h(p) \\ \alpha_2(t,h)=\phi_{-t} \circ \psi_h \circ \phi_h(p) \\ \alpha_3(t,h) = \psi_{-t} \circ \phi_{-h} \circ \psi_h \circ \phi_h(p) \end{array}$$ so that $c(t)= \alpha_3(t,t)$. Noticing that $$\begin{array}{l} \alpha_2(0,t)= \alpha_1(t,t) \\ \alpha_3(0,t)= \alpha_2(t,t) \end{array}$$ and for any $f \in C^{\infty}(M)$ $$\begin{array}{ll} \partial_t(f \circ \alpha_1) = Yf \circ \alpha_1 & \partial_t(f \circ \alpha_2)=-Xf \circ \alpha_2 \\ \partial_t(f \circ \alpha_3)=-Yf \circ \alpha_3 & \partial_h(f \circ \alpha_1)(0,h)=Xf(\alpha_1(0,h)) \end{array}$$ the identities $c'(0)=0$ and $c''(0)=2[X,Y]_p$ are shown using differential calculus.

Then, the identity $[X,Y]_p = \frac{d}{dt}_{|t=0} \psi_{-\sqrt{t}} \circ \phi_{-\sqrt{t}} \circ \psi_{\sqrt{t}} \circ \phi_{\sqrt{t}}(p)$ can be deduced from the previous one using the following lemma (Ex. 16, p. 176):

Lemma: Let $c : \mathbb{R} \to M$ be a smooth curve satisfying $c'(0)=0$. If $\gamma(t)=c(\sqrt{t})$, then $$\lim\limits_{h \to 0^+} \frac{\gamma(h)- \gamma(0)}{h}= \frac{1}{2}c''(0)$$

In fact, because we only consider $f \circ c$ where $f \in C^{\infty}(M)$, it is sufficient to show the lemma for $c : \mathbb{R} \to \mathbb{R}$. But $$c(h)=c(0)+ \underset{=0}{\underbrace{c'(0)}} \cdot h+ \frac{1}{2}c''(0) \cdot h^2+o(h^2)$$ implies $$\frac{c(\sqrt{h})-c(0)}{h}= \frac{1}{2}c''(0)+o(1).$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.